Packaging Design for Tradisional Snack (Object Study Kampung Kue Surabaya) - A. Solicitor; Widyasari; A. Sutejo (Nusantara Science and Technology Proceedings)
Indonesia has a wide variety of cultures, and one of them is traditional snacks. This culture can be a unique tourist attraction asset, so it must be maintained and preserved. Kampung Kue is one of the villages that produces the best quality and complete variety of traditional snacks in Surabaya. Along with the increasing needs of traditional snacks, the production of Kampung Kue‘s traditional snack is also increasingly diversified. All of the traditional snack produced by Kampung Kue are competing and trying to win the market, where consumers are faced with the many choices available on the market, so that the treatment of traditional snacks products must be increased, and such effort can be obtained through a unique traditional snacks packaging design. The main problem of Kampung Kue traditional snacks is that they are only wrapped individually using transparent resealable plastic wrap. The traditional snacks bought were only wrapped in as plastic bag, unless the customer buy them in very large quantity. They are also lacking in the knowledge about how the snack characteristics can affect the choice of the packaging. Therefore, it is necessary to conduct training to create a new packaging design that fits with the standard of good packaging.